Explaining Individual Differences in Advantageous Inequity Aversion by Social-Affective Trait Dimensions and Family Environment. Issue 2 (March 2022) - Yu, Hongbo; Lu, Chunlei; Gao, Xiaoxue; Shen, Bo; Liu, Kui; Li, Weijian; Xiao, Yuqin; Yang, Bo; Zhao, Xudong; Crockett, Molly. J.; Zhou, Xiaolin
Humans are averse to both having less (i.e., disadvantageous inequity aversion [IA]) and having more than others (i.e., advantageous IA). However, the social-affective traits that drive individual differences in IA are not well understood. Here, by combining a modified dictator game and a computational model, we found in a sample of incarcerated adolescents ( N = 67) that callous-unemotional traits were specifically associated with low advantageous but not disadvantageous IA. We replicated and extended the finding in a large-scale university student sample ( N = 2, 250) by adopting a dimensional approach to social-affective trait measures. We showed that advantageous IA was strongly and negatively associated with a trait dimension characterized by callousness and lack of social emotions (e.g., guilt and compassion). A supportive family environment negatively correlated with this trait dimension and positively with advantageous IA. These results identify a core set of social-affective dimensions specifically associated with advantageous IA.